Nowe autodafe. Zmediatyzowane incydenty publicznego palenia przedmiotów w archidiecezjach gdańskiej i przemyskiej (Przegląd Religioznawczy – The Religious Studies Review, 2020)
This article will present two media incidents that occurred in April 2019 in two dioceses of the Catholic Church in Poland. These events share several features, one of which – the burning of objects (which I described as modern autodafe) – is an important connecting factor. The purpose of the article will be cultural, media and religious studies analysis of these events.